To recruit skilled workers or to train one's own? Vocational training in the face of uncertainty as to the rate of retention of trainees on completion of training - Lutz Bellmann; Florian Janik (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2007)
The article deals with the impact of uncertainty as regards the retention of trainees completing vocational training programmes on firms' training behaviour. As an alternative to vocational training, the external recruitment of skilled workers is considered via an opportunity costs approach. The uncertainty is traced back to staff turnover, considerable product market competition and changing skill requirements. Indicators of these causes of uncertainty are examined as to their impact on vocational training and the recruitment of skilled workers with a fractional logit model, using a seemingly unrelated cluster-adjusted sandwich estimator with data from the IAB Establishment Panel. There is no confirmation that the presumed correlations exist in manufacturing. A negative correlation is identified in the service sector between high staff turnover coupled with rapid change in the skills required on the one hand, and commitment to vocational training on the other, while there is a positive link with the external recruitment of skilled workers. This is interpreted as an indication that uncertainty with regard to retention after training can go some way towards explaining the growing gap between employment and vocational training in the tertiary sector.
Keywords: 330; Betrieb; Personalpolitik; betriebliche Berufsausbildung; Ausbildungsverhalten; Auszubildende; Ausbildungsabsolventen; beruflicher Verbleib; zwischenbetriebliche Mobilität; Arbeitsplatzwechsel; Qualifikationsanforderungen; Personaleinstellung; Fachkräfte; verarbeitendes Gewerbe; Dienstleistungsbereich; Bildungsökonomie; IAB-Betriebspanel